Antiphospholipid antibodies: a risk factor for occlusive ocular vascular disease in systemic lupus erythematosus and the 'primary' antiphospholipid syndrome. Issue 5 (May 1989) - Asherson, R A; Merry, P; Acheson, J F; Harris, E N; Hughes, G R
Abstract : Seven cases of occlusive ocular vascular disease affecting retinal and choroidal vessels were found among 84 consecutive patients with raised levels of anticardiolipin antibodies attending the lupus arthritis clinic at St Thomas's Hospital from 1985 to 1987. Six patients with systemic lupus erythematosus (SLE) and one with a 'primary antiphospholipid syndrome' had occlusive ocular vascular disease affecting a variety of vessels. This gives a prevalence of occlusive ocular vascular disease of 8% in this subgroup of patients, significantly higher than the 0.5-2.0% previously reported in patients with SLE. Four of these patients also suffered from cerebrovascular disease, supporting the previously documented association between occlusive ocular vascular disease and central nervous system disease in SLE. Additionally, other features of the antiphospholipid syndrome were frequently present. These findings suggest that patients with SLE and raised anticardiolipin antibodies have a higher risk of developing occlusive ocular vascular disease than has been previously reported.